Analisis Faktor Pendukung dan Penghambat Pembelajaran Online Saat Pandemi diMA Midanutta'lim Mayangan Jogoroto - Rohmah, Hidayatur; Azizah, Nur Hafidhotul (Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study is to find out the supporting and inhibiting factors for online learning during the pandemic at MA Midanutta'lim Mayangan Jogoroto. This research is a qualitative study with descriptive analysis techniques. The results of this study are the COVID-19 pandemic has had a very large impact on the learning process, learning that is usually carried out directly is now being shifted to online learning by planning and implementing, the planning is to make materials and social evaluations,while the implementation is to distribute materials and assignments. to the WhatsApp group. Students feel bored and bored while carrying out learning. Online learning conducted for elementary school age children is considered less effective. There are several factors that support teachers in the online learning process, namely the availability of mobile phones, quotas and a stable internet network. In addition to the factors that support online learning, there are also several inhibiting factors for teachers in online learning. The inhibiting factors include not all students have cellphones and there are still many parents who are busy working.